Accelerating the pace of discovery in orthopaedic research: A vision toward team science. Issue 10 (5th June 2016) - Bahney, Chelsea S.; Bruder, Scott P.; Cain, Jarrett D.; Keyak, Joyce H.; Killian, Megan L.; Shapiro, Irving M.; Jones, Lynne C.
ABSTRACT: The landscape of basic science in the United States and around the world is changing, and the field of orthopaedic research is positioned to lead by embracing a culture of collaborative, team science that reflects our field's interdisciplinary nature. In this article we hope to address some of the cultural challenges and programmatic barriers that impede a team science approach in the US and suggest opportunities for change. © 2016 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 34:1673–1679, 2016.